LSI guided-high power short duration is safe and improves pulmonary vein isolation efficiency. (14th October 2021) - Di Cori, A; Della Volpe, S; Parollo, M; Mazzocchetti, L; Giannotti, M; De Lucia, R; Segreti, L; Viani, S; Paperini, L; Canu, A; Grifoni, G; Cellamaro, T; et al.
Abstract: Introduction: High-power short-duration (HPSD) is an increasingly used ablation strategy for pulmonary vein isolation (PVI) procedures, but Lesion Index (LSI)-guided HPSD radio-frequency (RF) application has not been described in this clinical setting. Purpose: We evaluated the procedural efficiency and safety of an LSI-guided HPSD strategy for atrial fibrillation (AF) ablation. Methods: Paroxysmal and persistent AF patients scheduled for AF ablation were prospectively enrolled and divided in two groups, according to the ablation power used. The LSI-HP Group included patients ablated with a RF power of 50 Watts and the LSI-LP Group included patients ablated with 35 Watts. All patients underwent only PVI under LSI guidance (LSI between 5.5 and 6 anteriorly; LSI between 4.5 and 5 posteriorly) with a point by point strategy and an inter-lesion distance <6 mm. Procedural efficiency parameters were compared between groups. Results: Forty-six patients with AF (60% paroxysmal) were prospectively enrolled, 25 in the LSI-HP Group and 21 in the LSI-LP Group. They were usually male (78%) with a low-intermediate CHA2DS2-Vasc score (1.8±1.1), a preserved ejection fraction (60±6%) and moderate left atrial dilatation (45±6 mm). Baseline clinical characteristics resulted comparable between groups (p=NS). PVI was successful in all patients. RF time (30.22±9.04 vs 47.85±11.87 min, p<0.0001), total procedure time (138.7±33.2 vs 177.6±49.77, p=0.006) and fluoroscopy time (13.92±5.34 vs 23.14±10.97 min, p=0.006) were significantly lower in the LSI-HP Group. No complication or steam pops was seen in either group. Conclusions: LSI-HP AF ablation significantly improves procedural efficiency, reducing ablation time, total procedural duration and fluoroscopy use, while maintaining a comparable safety profile as lower powers. Funding Acknowledgement: Type of funding sources: None.